Pengaruh Pengetahuan Investasi, Modal Investasi dan Motivasi Investasi Terhadap Minat Investasi di Pasar Modal Pada Mahasiswa Fakultas Ekonomi dan Bisnis yang Terdaftar di Galeri Investasi Universitas Warmadewa - Surya Arika Saputra; I Ketut Darma; I Gusti Lanang Putu Tantra (Warmadewa Economic Development Journal (WEDJ), 2023)
This study aims to determine the effect of knowledge, capital and motivation on interest in investing in the capital market in FEB students registered at the Warmadewa University Investment Gallery. This research is a quantitative research involving data collection and statistical analysis using primary and secondary data. Data collection techniques used in the form of questionnaires and surveys involving 100 active students. Researchers will send surveys online to students who already have an account. Based on the results of the study, investment knowledge has no significant impact on the interest in investing in the capital market for students enrolled in the Investment Gallery. Where it shows students with good investment knowledge are significantly more interested in investing than students with less knowledge. Students enrolled in the Investment Gallery do not show a significant relationship between investment capital and interest in the capital market. The motivation of FEB students to invest in the capital market is positively correlated with investment interest.